istme - Törnquist-Plewa, Barbara 1960-; Bernsand, Niklas 1973-; La Rosa, Marco (Lund University, Centre of European Studies at Lund University, 2017)
This volume is one of the outcomes of the network project In Search for Transnational Memory in Europe (ISTME), which was financed during four years 2012-2016 by a grant from COST (European Cooperation in Science and Technology) as COST Action IS1203. The Centre for European Studies (CFE) at Lund University was grant holder for ISTME, and the Centre's Head Prof. Barbara Törnquist-Plewa was chair. ISTME gathered researchers from 36 countries in Europe. The volume opens with a short report of the activities of the action delivered by the chair at the final conference of ISTME in Dublin 1-3 September 2016. It is followed by a selection of papers presented at the action's conferences and workshops (see the report in this volume). Most papers written by the action participants have been aimed for one of the five publications (two collected volumes and three special issues of scientific journals) prepared by the action or became included in other academic publications. However, several papers were published electronically on the action's website, and it is a sample of those publications that are featured in this volume. The concluding chapter constitutes an attempt to look ahead and reflect over current and possible future directions in Memory Studies. It emerged in connection to the conference "Thinking through the future of Memory", 3-5 December 2016, inaugurating the Memory Studies Association, which was initiated by a group of participants in our COST Action.
Keywords: Geschichte 2012-2016; Kollektives Gedächtnis; Interkulturalität; Europa; Konferenzschrift